Prophylactic transarterial chemoembolization after R0 resection is beneficial to improve the prognosis in hepatocellular carcinoma patients with microvascular invasion - Wenjie Sun; Yafang Li; Haozhe Fu; Jiangze Li; Jinbao Li (Discover Oncology)
Abstract Objective Microvascular invasion (MVI) is a risk factor for disease recurrence and worse survival in hepatocellular carcinoma (HCC) patients after radical resection. This study aimed to investigate the efficacy of prophylactic transarterial chemoembolization (TACE) after R0 resection in HCC patients with MVI. Methods A total of 130 HCC patients with MVI who received R0 resection were retrospectively analyzed, and categorized into TACE (n = 73) and non-TACE (n = 57) groups according to whether prophylactic TACE after R0 resection was performed or not. Tumor recurrence, death, recurrence-free survival (RFS), and overall survival (OS) were evaluated. Results Tumor grading (P = 0.001), minor axis of tumor (P = 0.017), neutrophil (P = 0.029), and aspartate aminotransferase (P = 0.014) were higher in TACE group compared to non-TACE group at baseline, indicating a worse baseline disease condition in TACE group. During the follow up, tumor recurrence rate (56.2% versus 61.4%, P = 0.548), mortality rate (37.0% vs. 43.9%, P = 0.427), RFS (median: 44.0 versus 37.0 months, P = 0.325), and OS (median not reached in both groups, P = 0.355) were not different between TACE and non-TACE groups. Considering the worse baseline disease condition in TACE group versus non-TACE group as confounding factor, that affects the evaluation of efficacy; the multivariable Cox regression analyses were performed for adjustment, which revealed that group (TACE versus non-TACE) was independently correlated with prolonged RFS (P = 0.007, HR = 0.447, 95% CI: 0.248–0.804) and OS (P = 0.001, HR = 0.260, 95% CI: 0.116–0.583). Conclusion Prophylactic TACE after R0 resection is beneficial to improve the prognosis in HCC patients with MVI. However, further large-scale, randomized, controlled studies are needed for verification.